A STUDY OF IDEALISTIC ATTITUDES IN NISAR AZIZ BUTT'S URDU NOVELS - Dr. Muhammad Rahman; Dr. Mutahir Shah; Dr. Bismina Siraj; Dr. Saira Irshad; Syed Azwar Abbas (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
Nisar Aziz Butt was a prominent novelist of Urdu literature. She introduced many important novels to Urdu Fiction. These novels include "Nagri Nagri Phira Musafir", "Nay Chiraghay Nay Gulay" and "Driya Kesing". There are more idealistic attitudes in these novels. Due to these attitudes, the atmosphere of her novels has changed. Similarly, a new trend has emerged in the characters of his novels. This is the reason that she has expressed his feelings and emotions through these characters.